A collection of inducible transcription factor‐glucocorticoid receptor fusion lines for functional analyses in Arabidopsis thaliana. (21st May 2022) - Shimada, Setsuko; Yanagawa, Yuki; Munesada, Takachika; Horii, Yoko; Kuriyama, Tomoko; Kawashima, Mika; Kondou, Youichi; Yoshizumi, Takeshi; Mitsuda, Nobutaka; Ohme‐Takagi, Masaru; Makita, Yuko; Matsui, Minami
SUMMARY: Arabidopsis possesses approximately 2000 transcription factors (TFs) in its genome. They play pivotal roles in various biological processes but analysis of their function has been hampered by the overlapping nature of their activities. To uncover clues to their function, we generated inducible TF lines using glucocorticoid receptor (GR) fusion techniques in Arabidopsis. These TF‐GR lines each express one of 1255 TFs as a fusion with the GR gene. An average 14 lines of T2 transgenic TF‐GR lines were generated for each TF to monitor their function. To evaluate these transcription lines, we induced the TF‐GR lines of phytochrome‐interacting factor 4, which controls photomorphogenesis, with synthetic glucocorticoid dexamethasone. These phytochrome‐interacting factor 4‐GR lines showed the phenotype described in a previous report. We performed screening of the other TF‐GR lines for TFs involved in light signaling under blue and far‐red light conditions and identified 13 novel TF candidates. Among these, we found two lines showing higher anthocyanin accumulation under light conditions and we examined the regulating genes. These results indicate that the TF‐GR lines can be used to dissect functionally redundant genes in plants and demonstrate that the TF‐GR line collection can be used as an effective tool for functional analysis of TFs. Significance Statement: We generated inducible transcription factor (TF) lines in Arabidopsis, TF‐glucocorticoid receptor (GR) lines, each expressing one of 1255 TFs as a fusion with the GR gene that affects transportation to the nucleus by application of an inducer, dexamethasone. After evaluating these lines by examination of phytochrome‐interacting factor 4, we performed screening for TFs involved in light signaling from the TF‐GR lines and analyzed two that showed higher anthocyanin accumulation under light conditions.